(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The English mined is a melange, but one that is constantly reshaping and evolving, whether through internal changes or external external transform, in this case borrowings from Turkic. This is a historical study of the mapping of Turkic on English, with a survey of Turkic loanwords as reflections of the diversity of English. This paper employs a historical linguistic approach to review the sociocultural and historical determinants, which were contributing for the adoption of Turkic lexicon into English.